Mosaic ACVRL1 and ENG mutations in hereditary haemorrhagic telangiectasia patients. Issue 5 (4th March 2011) - Best, D Hunter; Vaughn, Cecily; McDonald, Jamie; Damjanovich, Kristy; Runo, James R; Chibuk, Jason M; Bayrak-Toydemir, Pinar
Abstract : Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant disorder caused by mutations in the ACVRL1, ENG, and SMAD4 genes. HHT is commonly characterised by small arteriovenous malformations (AVMs) known as telangiectasias of the skin, oral or gastrointestinal mucosa, as well as larger AVMs of solid organs (lungs, liver, brain). However, the manifestations of HHT are extremely variable. Two patients with no family history of HHT and strikingly different clinical presentations, who are mosaic for mutations in the ACVRL1 or ENG gene, are reported here. These cases represent the first report of mosaicism in patients clinically affected with classical HHT and pulmonary arterial hypertension, and suggest the need for awareness of mosaicism when performing clinical testing for this disorder.